2015
DOI: 10.1155/2015/135689
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Accuracy of Different Techniques for the Laboratory Diagnosis of Schistosomiasis Mansoni in Areas of Low Endemicity in Barra Mansa City, Rio de Janeiro State, Brazil

Abstract: Schistosomiasis constitutes a major public health problem, with an estimated 200 million people infected worldwide. Many areas of Brazil show low endemicity of schistosomiasis, and the current standard parasitological techniques are not sufficiently sensitive to detect the low-level helminth infections common in areas of low endemicity (ALEs). This study compared the Kato-Katz (KK); Hoffman, Pons, and Janer (HH); enzyme-linked immunosorbent assay- (ELISA-) IgG and ELISA-IgM; indirect immunofluorescence techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 61 publications
0
29
0
2
Order By: Relevance
“…Second, the use of the Kato-Katz method to diagnose schistosomiasis in areas of low endemicity has been questioned. Some authors suggest that more sensitive techniques, such as ELISA, should be used [26]. However, the prolonged presence of reactive IgM after treatment and the death of the worms is a critical problem in evaluating the effectiveness of an intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the use of the Kato-Katz method to diagnose schistosomiasis in areas of low endemicity has been questioned. Some authors suggest that more sensitive techniques, such as ELISA, should be used [26]. However, the prolonged presence of reactive IgM after treatment and the death of the worms is a critical problem in evaluating the effectiveness of an intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The Kato-Katz method was used [25]. This predominant method for detecting S. mansoni eggs is relatively straightforward, inexpensive and highly specific [26–29]. Valid stool samples were those for which the stool quantity was sufficient to allow the sample to be processed via the Kato-Katz method.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that a diagnostic test with high specificity and sensitivity will be needed for prevention, control and elimination of this disease [7, 12]. Some diagnostic methods have already shown their ability to detect positive individuals missed by parasitological techniques, due to low or absence of egg excretion [13, 14, 19]. Immunoassays based on antigen or antibody detection have been the most studied, due to high sensitivity and ease-of-translation to a format applicable to field settings [60].…”
Section: Discussionmentioning
confidence: 99%
“…Serum immunoreactivity to schistosome antigens allows detection of infections with loads as low as 1 epg. Even though the antibody-detection methods are currently not the first choice for endemic areas, due to their inability to discriminate current infection from previous exposure, as well as the inability to monitor treatment effectiveness, they have been accepted as a complementary tool during epidemiological survey [13, 19, 34, 62]. One of the difficulties in developing antibody-detection methods is the choice of antigen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation